2004
DOI: 10.1074/jbc.m403202200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Methanothermobacter thermautotrophicus Minichromosome Maintenance (MCM) Helicase N-terminal Domains

Abstract: Minichromosome maintenance helicases are ringshaped complexes that play an essential role in archaeal and eukaryal DNA replication by separating the two strands of chromosomal DNA to provide the singlestranded substrate for the replicative polymerases. For the archaeal protein it was shown that the N-terminal portion of the protein, which is composed of domains A, B, and C, is involved in multimer formation and singlestranded DNA binding and may also play a role in regulating the helicase activity. Here, a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 36 publications
2
77
0
Order By: Relevance
“…A very similar static threefold symmetric ring is observed for the Nterminal domains of the DnaB homolog G40P [50]. Notably, the N-terminal domain of an archaeal MCM protein forms a nearly sixfold symmetric ring that is crucial for hexamerization of this complex [47,51]. This ring is formed by an OB-fold, which is interesting as this is the proposed exit side of the helicase [52], and this region could conceivably play a role in interacting with extruded single-stranded DNA.…”
Section: Intersubunit Interactionsmentioning
confidence: 53%
See 1 more Smart Citation
“…A very similar static threefold symmetric ring is observed for the Nterminal domains of the DnaB homolog G40P [50]. Notably, the N-terminal domain of an archaeal MCM protein forms a nearly sixfold symmetric ring that is crucial for hexamerization of this complex [47,51]. This ring is formed by an OB-fold, which is interesting as this is the proposed exit side of the helicase [52], and this region could conceivably play a role in interacting with extruded single-stranded DNA.…”
Section: Intersubunit Interactionsmentioning
confidence: 53%
“…In the case of T7gp4, oligomerization is mediated by an extended 'tail' that appends the primase domain and sits on the adjacent subunit [36 ]. Oligomerization of DnaB, the SF3 helicases [46], and MCM proteins [47] appears to derive from a second domain that is static and also forms tight and extensive interactions with adjacent subunits through apparently inflexible interfaces. These properties classify this region as a 'collar' similar to that described earlier in the case of clamp-loaders [48,49].…”
Section: Intersubunit Interactionsmentioning
confidence: 99%
“…As is typical for DNA helicases, but in contrast to Mcm2-7 (22,58,218), ATP hydrolysis is stimulated by the addition of either ssDNA or dsDNA (42,125,174).…”
Section: Atp Hydrolysis and Allosteric Interactionsmentioning
confidence: 99%
“…Biochemical studies with the various Mcm protein complexes in yeast and mammals have shown that a dimeric complex of Mcm467 heterotrimer contains 3Ј 3 5Ј helicase, ssDNA binding, and DNA-dependent ATPase activities, whereas its interaction with either Mcm2 or Mcm3-5 inhibit the helicase activity (19,22,62). The Mcm complex is believed to function as a replicative helicase of Eukaryote and Archaea (18,19).…”
Section: Figmentioning
confidence: 99%